Two new species of Lasianthus (Rubiaceae) from Hoang Lien National Park, northern Vietnam - Dang, Van-Son; Naiki, Akiyo (Phytotaxa, 2019)
Two new species, Lasianthus fansipanensis V.S. Dang & Naiki and Lasianthus sapaensis V.S. Dang & Naiki (sect. Nudiflorae), were discovered in the Hoang Lien National Park of northern Vietnam and are here described and illustrated. Colour photographs, preliminary conservation assessment, and tables comparing these two new species against two closely related species are also presented.